Sinergi Multi Stakeholder dalam Mewujudkan Community Development Melalui Program Holcim Integrated Farming (Studi pada Corporate Social Responbility PT Holcim Indonesia Tbk Tuban Plant) - Santiko, Dedy (Jurnal Administrasi Publik, 2015)
Abstract: The Synergy Multi Stakeholders in Manifasting Community Development Through the Program of Holcim Integrated Farming (HIFA) (Studies on CSR Holcim Tuban). This study describes the corporate social responsibility which has been implemented by Holcim tuban through HIFA program. The program is a new alternative livelihood for the people in the form of dairy farms by establishing partnerships with multiple stakeholders. The result of this research is the implementation of the program HIFA and synergy among stakeholders in realizing real community development is appropriate. However there are still some problems, among which the first, netting goals are not evenly to the entire community ring 1. Second, the difficulty of selling cattle by WMU after harvest which resulted in delays in repayment of the loan to BSM. And third, the crops of farmers who varied as a result of farmers own mindset. Keyword: corporate social responbility, community development, holcim integrated farming Abstrak: Sinergi Multi Stakeholder dalam Mewujudkan Community Development melalui Program Holcim Integrated Farming (HIFA) (Studi pada CSR Holcim Tuban). Penelitian ini menjelaskan tentang tanggung jawab sosial perusahaan yang telah diterapkan oleh holcim tuban melalui program HIFA. Program ini merupakan program alternatif mata pencaharian baru bagi masyarakat dalam bentuk peternakan sapi dengan menjalin kemitraan dengan beberapa stakeholder. Hasil dari penelitian ini yaitu pelaksanaan program HIFA dan sinergi antar stakeholder dalam mewujudkan community development sebenarnya sudah sesuai. Namun masih terdapat beberapa masalah, diantaranya yaitu pertama, penjaringan sasaran yang tidak merata kepada seluruh masyarakat ring 1. Kedua, sulitnya penjualan sapi oleh WMU setelah panen yang mengakibatkan keterlambatan pelunasan pinjaman kepada BSM. Dan ketiga, hasil panen dari peternak yang variatif akibat dari mindset peternak sendiri. Â  Kata kunci: corporate social responbility, community development, holcim integrated farming